Follow Me, Mittens - Schaefer, Lola M. 1950-; Hartung, Susan Kathleen (New York : HarperCollinsPublishers, 2007)
Mittens the kitten goes for a walk with Nick, but he is distracted by a butterfly and becomes lost.
Accelerated Reader AR